BATU SINDU, SELAYANG PANDANG - Nenggih Susilowati (Berkala Arkeologi Sangkhakala, 2006)
Actually, Batu Sindu was an important site that was known throughfolktales and beautiful view. As the condition of the environment, BatuSindu was a dwelling site, and it also indicated as a neolitic site as thefinding of earthenware fragments, square adze and grindingstone.